Meningkatkan Kepuasan Pelanggan melalui Strategi dan Kebijakan Bisnis pada UMKM Ayam Gepuk Pak Gembus Telkom University - Sitohang, Fitri Melani; Rahmawati, Nurul; Abram, Marcellino; Choiruman, Doni; Dary, Muhammad; Nadhif, Muhammad (ARZUSIN, 2025)
This study aims to identify the root causes of low customer ratings for UMKM Ayam Gepuk Pak Gembus and provide recommendations to improve product quality, service, and facilities. The study employed a qualitative research method with primary data gathered through observation and interviews. Root Cause Analysis (RCA) identified three major factors impacting customer satisfaction: product quality, service quality, and facilities. Findings indicate that inconsistency in taste and unsatisfactory chili sauce are primary complaints. Additionally, poor queue management, extended waiting times, and unfriendly staff negatively affect service ratings. Facility issues such as cleanliness, cramped layout, and limited parking hinder customer comfort. Poor financial management emerged as the root cause, affecting overall operations. Recommendations include improving financial management, standardizing product quality, providing customer service training, reorganizing facilities, and addressing customer reviews. These strategies aim to enhance customer satisfaction, improve ratings, and achieve sustainable business growth.